2018
DOI: 10.1097/qad.0000000000001754
|View full text |Cite
|
Sign up to set email alerts
|

The growing burden of noncommunicable disease among persons living with HIV in Zimbabwe

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 22 publications
3
64
1
Order By: Relevance
“…In addition, the evidence from high‐income countries cannot easily be extrapolated to sub‐Saharan Africa because the epidemic in high‐income countries is largely restricted to key populations who likely differ in important ways from the general population in sub‐Saharan Africa. Several studies have investigated the association between HIV and NCDs in individual African countries , but were limited to only certain regions of single countries using short time spans. One systematic review and meta‐analysis of the association between ART use and hypertension and diabetes mellitus in sub‐Saharan Africa , based on 20 cross‐sectional studies, found that ART is associated with dyslipidaemia, but not with hypertension and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the evidence from high‐income countries cannot easily be extrapolated to sub‐Saharan Africa because the epidemic in high‐income countries is largely restricted to key populations who likely differ in important ways from the general population in sub‐Saharan Africa. Several studies have investigated the association between HIV and NCDs in individual African countries , but were limited to only certain regions of single countries using short time spans. One systematic review and meta‐analysis of the association between ART use and hypertension and diabetes mellitus in sub‐Saharan Africa , based on 20 cross‐sectional studies, found that ART is associated with dyslipidaemia, but not with hypertension and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…[30] As the life expectancy of HIV-positive individuals continues to increase, it is important to monitor non-communicable comorbidities such as CVD, hypertension, diabetes, chronic obstructive pulmonary disease, kidney disease and cancer, owing to the increased risk of development at younger ages than is typical in HIV-negative patients. [31][32][33][34][35][36] While these differences were not found in our study population, we suspect that this is because the ED patients in this study may have represented a younger HIV-positive cohort.…”
Section: Researchmentioning
confidence: 99%
“…[4] HIV-positive individuals are predicted to have a 26% increased likelihood of being diagnosed with at least one NCD over time (33% in 2015, 59% in 2035), compared with a 6% increase in likelihood for HIV-negative individuals (14% in 2015, 20% in 2035). [5] In addition, antiretroviral (ARV) medications are known to have a number of complications that predispose PLWH to developing cardiovascular, neurological, muscular, liver, bone and/or immune system disorders as a result of accumulated drug toxicity. [4,6] Current research on HIV infection and associated comorbidities also points towards an increasingly high baseline prevalence of NCDs and other comorbidities in specific populations of interest.…”
Section: Researchmentioning
confidence: 99%
“…Recent studies have documented the substantial burden of depression in resource-limited settings, which can result in not only significant disability, but also premature mortality [2]. Depression is often a co-morbid condition with other chronic illnesses, such as cancer, diabetes, and HIV [3][4][5]. In a meta-analysis of ten studies, people living with HIV experienced a twofold increase in risk of major depressive disorder (MDD) compared to those who were HIV-negative [6].…”
Section: Introductionmentioning
confidence: 99%